Safety of alemtuzumab in a nationwide cohort of Finnish multiple sclerosis patients - Rauma Ilkka; Mustonen Tiina; Seppä Juha Matti; Ukkonen Maritta; Männikkö Marianne; Verkkoniemi-Ahola Auli; Kartau Marge; Saarinen Jukka T.; Luostarinen Liisa; Simula Sakari; Ryytty Mervi; Ahmasalo Riitta; et al. (SPRINGER HEIDELBERG, 2022)
Background
Alemtuzumab is an effective disease-modifying therapy (DMT) for highly active multiple sclerosis (MS). However, safety concerns limit its use in clinical practice.
Objectives
To evaluate the safety of alemtuzumab in a nationwide cohort of Finnish MS patients. Methods In this retrospective case series study, we analyzed the data of all but two MS patients who had received alemtuzumab in Finland until 2019. Data were systematically collected from patient files.
Results
Altogether 121 patients were identified, most of whom had received previous DMTs (82.6%). Median follow-up time after treatment initiation was 30.3 months and exceeded 24 months in 78 patients. Infusion-associated reactions (IARs) were observed in 84.3%, 57.3%, and 57.1% of patients during alemtuzumab courses 1-3, respectively. Serious adverse events (SAEs) were observed in 32.2% of patients, serious IARs in 12.4% of patients, and SAEs other than IARs in 23.1% of patients. Autoimmune adverse events were observed in 30.6% of patients. One patient died of hemophagocytic lymphohistiocytosis, and one patient died of pneumonia. A previously unreported case of thrombotic thrombocytopenic purpura was documented.
Conclusions
SAEs were more frequent in the present cohort than in previous studies. Even though alemtuzumab is a highly effective therapy for MS, vigorous monitoring with a long enough follow-up time is advised.